Flow and heat transfer performance of supercritical pressure carbon dioxide in pipes with discrete double inclined ribs. (March 2020) - Yuan, Nan; Bi, Dapeng; Zhai, Yuling; Jin, Yajuan; Li, Zhouhang; Wang, Hua
Highlights: Evaluated the effectiveness of discrete ribs in enhancement of heat transfer to SCO2 . Performed sensitivity analysis on geometrical parameters of discrete ribs. Discrete ribs caused strong inhibition on both positive and negative effects of buoyancy. Overall thermal performance of ribbed pipe varied with the magnitude of buoyancy force. Bo * was recommended for the optimization of SCO2 heat transfer enhancement techniques. Abstract: Heated flow of supercritical pressure carbon dioxide in pipes with discrete double inclined ribs (DDIR) were numerically studied in this work. The turbulent flow and heat transfer was solved by a modified Shear Stress Transport k-ω model, where a variable turbulent Prandtl number formulation was incorporated. The model accuracy was verified by experimental data covering wide working conditions. Numerical runs were performed at 7.58 MPa, mass flux of 200 ~ 800 kg /(m 2 s), and heat flux of 56.7 kW/m 2 . Results show that the strong buoyancy effect existing in smooth pipes was heavily inhibited by DDIR and no serious deterioration occurred. Sensitivity analysis on geometrical parameters suggest that the rib spacing the most sensitive one to the occurrence of heat transfer deterioration. The influence of inclination angle was much weaker than the rib height and spacing. The overall thermal performance of the DDIR pipe was the best when Bo * was around 4.5 × 10 −6, with a PEC of 3~4. In the regions with very strong or negligible buoyancy, however, PEC was a much lower value between 1~2. The major role of discrete ribs is to interrupt the continuous development of near-wall buoyant layer and subsequently eliminate the negative effect of buoyancy on heat transfer. Ribs cannot effectively increase the positive effect of buoyancy on heat transfer. Finally, Bo * was found to be appropriate for the performance evaluation and optimization of enhancement techniques for supercritical heat transfer.